Frequency modulated continuous wave radar systems for detection and tracking: a review - Ibrahimy, Abdullah Faruq Ibn; Ismail, Ahmad Fadzil; Ibrahimy, Muhammad Ibn (GEOMATE International Society, 2020)
The technology has recently developed for producing portable radar system. This portable radar system can be used for security and safety management systems. It can achieve many functionalities, but which could only be achieved by bulky radar systems. Portable frequency modulated continuous wave radar can provide us high motion detection sensitivity, good signal to noise ration and range detection capability. Nonlinearities in the beat signal worsen range resolution because target energy is distributed through different frequencies. This outcome usually rises at a higher range when there is less correlation between the transmitted and received signals. This paper proposes a method for reducing nonlinearities in the beat signal for improving range detection capability of a frequency modulated continuous wave radar system.